1981
DOI: 10.3109/00048678109159425
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Obsessional Neurosis in a Family Setting

Abstract: The limitation of a patient-centered approach to the treatment of obsessive-compulsive disorders are underlined by the failure of modern behaviour therapy techniques to help usefully more than 50 per cent of patients. The concept of family homeostasis is discussed in relation to two cases of obsessive-compulsive neurosis which failed to respond to patient-centred treatment over several years. The successful treatment of these cases in a family context is described. It is suggested that the comparative success … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1985
1985
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…Exposure therapy may involve considerable discomfort as patients expose themselves to anxietyprovoking situations while at the same time refraining from performing the rituals that would reduce their anxiety. Estimates on the percent of patients who complete ERP and are helped by it range from 67 % to 90 % (Hafner et al 1981;Foa et al 1992), and estimates on drop-out rates range from 20 % to 25 % (Rachman and Hodgson 1980;Hafner et al 1981;McDonald et al 1988). Thus, this method may help only 50 % of patients with OCD (Hafner et al 1981).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Exposure therapy may involve considerable discomfort as patients expose themselves to anxietyprovoking situations while at the same time refraining from performing the rituals that would reduce their anxiety. Estimates on the percent of patients who complete ERP and are helped by it range from 67 % to 90 % (Hafner et al 1981;Foa et al 1992), and estimates on drop-out rates range from 20 % to 25 % (Rachman and Hodgson 1980;Hafner et al 1981;McDonald et al 1988). Thus, this method may help only 50 % of patients with OCD (Hafner et al 1981).…”
Section: Introductionmentioning
confidence: 98%
“…Estimates on the percent of patients who complete ERP and are helped by it range from 67 % to 90 % (Hafner et al 1981;Foa et al 1992), and estimates on drop-out rates range from 20 % to 25 % (Rachman and Hodgson 1980;Hafner et al 1981;McDonald et al 1988). Thus, this method may help only 50 % of patients with OCD (Hafner et al 1981). Exposure therapy may be less successful for patients with obsessions alone (Marks 1981), although more recent results based on speciÞc identiÞcation of mental rituals are better (Salkovskis and Westbrook 1989).…”
Section: Introductionmentioning
confidence: 98%
“…Case studies showed advantages to parental involvement in treatment for children and young adults. [37][38][39] In a controlled study with a small sample, Emmelkamp and DeLange 40 compared the outcome of Dutch clients treated behaviorally with or without the spouse as cotherapist. Unfortunately, the content of psycho-educational interventions aimed at reducing conflict or enhancing communication was not described.…”
Section: Family Treatment Interventionsmentioning
confidence: 99%
“…Rather than seeking a biochemical or hormonal explanation, it fits well with our clinical practice and observation of the expectations placed on women at a different stage of their life. The articles mentioned earlier by Hafner et al (1981) and Hafner (1982) actually focus upon the two different client groups -adolescents entrapped in their family of origin interactions, and older married women entrapped in pathological marital interactions -and recommend family therapy for the adolescent group and 'spouse aided therapy' for the married women's group. These papers will be considered in more detail later.…”
Section: Age Of Onsetmentioning
confidence: 99%
“…That is, a vicious cycle can be viewed as existing whereby the child is symptomatic because of the nature of the relationship with their parent(s); the parent(s) has an 'overinvolved' relationship with their child because of the nature of their symptoms. Hafner et al (1981) outlined two compelling case studies of young men with OCD. Both young men had chronic and severe OCD which had necessitated prolonged hospit-alisation and had not responded to a broad range of treatment options which were substantially behavioural.…”
Section: Systemic Approachesmentioning
confidence: 99%